Score twice before you cut once: a clinical case of reconstructive bariatric surgery after obesity surgery in a patient with postoperative hypothyroidism and hypoparathyroidism - N. I. Volkova; Yu. S. Degtyareva; M. A. Burikov (Медицинский вестник Юга России, 2021)
Hundreds of thousands of bariatric surgeries are performed worldwide every year. Th ey have long been proven to be safe and eff ective in treating obesity and type 2 diabetes. Along with an unconditional positive eff ect, these interventions, especially shunting ones, are characterized by specifi c complications. In the absence of proper correction, they can become fatal for patients. One of these complications is malabsorption leading to a defi ciency of vitamins and microelements, which in most cases, is amenable to timely correction in the postoperative period. However, there are situations when it is not possible to carry out an eff ective correction and it becomes necessary to perform reconstructive interventions with the reverse inclusion of the small intestine in the digestion, which is associated with great diffi culties. Th e authors demonstrated this situation in the description of clinical observation of a patient with postoperative hypothyroidism and history of postoperative hypoparathyroidism, who underwent bariatric surgery. Impaired absorption of drugs (L-thyroxine, calcium, and vitamin D), and therefore, uncompensated hypothyroidism and hypocalcemia was an indication for reconstructive surgery.